Long-term benefits of single left ventricular pacing based on rate-adaptive atrioventricular delay algorithm in cardiac resynchronization therapy - Yan, Xuejing; Ma, Xuejuan; Zhao, Lulu; Sun, Guihu; Zhao, Ling; Xu, Wenkai; Wang, Jing; Pu, Lijin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCurrent guidelines lack long-term evidence comparing single left ventricular pacing (LUVP) with standard biventricular pacing (BVP) in cardiac resynchronization therapy (CRT). This study evaluates the clinical superiority of rate-adaptive atrioventricular delay (RAAVD) algorithm-guided LUVP over BVP.MethodsIn this retrospective cohort study, 67 consecutive patients meeting the criteria for cardiac resynchronization therapy (CRT) with complete left bundle branch block (CLBBB) were enrolled between April 2013 and April 2023. They were assigned to either the right atrium-left ventricle dual-site pacing group (RAAVD LUVP, n = 42) or the biventricular pacing group (BVP, n = 25), with a median follow-up duration of 43.59 months. The primary endpoints included disease-related rehospitalization, device complications, and battery longevity. Secondary outcomes comprised cardiac structure, function, and synchrony.ResultsThere were no significant differences in baseline characteristics such as preoperative ejection fraction and cardiomyopathy type between the groups. The RAAVD LUVP group demonstrated significant advantages: i) Rehospitalization rate (23.8% vs. 48.0%, P = 0.041); ii) Zero device complications vs. 12% in BVP (P = 0.048), iii) Extended battery longevity (7.95 ± 0.78 vs. 4.66 ± 0.66 years, P < 0.001); iv) Cardiac function (LVEF: 45.7 ± 13.3% vs. 38.9 ± 10.6%, P = 0.034; The 6-minute walk distance: 414.50 ± 68.79 m vs. 379.04 ± 58.02 m; P = 0.034); v) Cardiac structure (LAD: 35.55 ± 7.11 mm vs. 39.96 ± 8.25 mm, P = 0.018; LVEDd: 60.10 ± 10.85 mm vs. 67.68 ± 9.40 mm, P = 0.01), and vi) Cardiac synchronization (paced QRS duration: 129.00 ± 18.78 vs. 147.96 ± 26.13 ms, P = 0.001; Ts-SD12: 96.66 ± 51.51 ms vs. 122.12 ± 52.29 ms; P = 0.034). Subgroup analysis revealed left bundle branch area pacing (LBBAP) further enhanced interventricular synchrony compared to lateral vein pacing (IVMD: 37.74 ± 21.24 vs. 53.11 ± 19.42 ms, P = 0.020).ConclusionThe dynamic integration of RAAVD LUVP with intrinsic conduction brings CRT closer to physiological states, which provides sustained clinical benefits compared to conventional BVP. The additional electromechanical advantages of LBBAP are related to the choice of anatomical location.